How I came to Sparkle again : a novel - McLaren, Kaya (St. Martin's Press, 2012)
Tells the story of three different women--Jill returning home after heartbreak, Lisa looking for real romance, and ten-year-old Cassie grieving her deceased mother--and their transition from loss to love in a small Colorado ski town named Sparkle.